Digital Asset Due Diligence in E-Commerce Mergers: A Comparative Antitrust Law Analysis of Indonesia and the United States - Hutagalung, Adriel Reyimer Samuel; Tabitha, Saulina Hariarani; Pandunata, Victor (SIGn Jurnal Hukum, 2025)
The integration of strategic digital assets, such as big data and algorithms, within e-commerce merger transactions creates new competition risks. These risks have not been adequately addressed by conventional due diligence regulations in Indonesia. This study aims to analyze the validity of sensitive information exchange during the pre-merger due diligence process viewed from an antitrust law perspective. Furthermore, this study identifies the legal implications of the oversight time-lag in the GoTo merger case. Utilizing a normative legal research method with statutory, comparative, and case approaches, this research compares the post-merger notification regime in Indonesia (Law Number 5 of 1999) with the gun-jumping doctrine and pre-merger notification mechanism in the United States (Sherman Act & HSR Act). The results indicate that the absence of a waiting period and specific rules regarding data exchange protocols in Indonesia renders the digital asset due diligence process highly risky. Such risks may serve as a vehicle for covert cartels or the premature transfer of beneficial ownership. The GoTo case study reveals that the integration of a digital ecosystem involving 55 million users’ data occurred prior to the KPPU determination. The determination was issued only 1 year after the transaction, thereby creating barriers to entry that went undetected at an early stage. This study concludes that there is a need to harmonize antitrust law with data protection law. This harmonization can be achieved by adopting the clean team mechanism and transitioning to a pre-merger notification system to prevent data monopolies in the digital economy.